PENGARUH DEFERRED TAX EXPENSE, DEBT COVENANT DAN FIRM SIZE TERHADAP MANAJEMEN LABA - Oktaviyanti Oktaviyanti; Prisila Damayanty (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study was to determine the effect of deferred tax expense, debt covenants and firm size partially and simultaneously on earnings management. The population in this study is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2020. Sampling in this study used a purposive sampling method with several predetermined criteria so that 15 companies were obtained as research samples. . The data analysis method consists of descriptive statistics, hypothesis testing (t test), coefficient of determination (R2), and F test with the help of the IBM SPSS Version 26 software program. Based on the results of the analysis, it shows that deferred tax expense partially has a significant positive effect on earnings management, the debt covenant variable partially has a significant positive effect on earnings management, while the firm size variable partially has a significant negative effect on earnings management. And simultaneously deferred tax expense, debt covenant and firm size have a significant positive effect on earnings management.